Fashion Marketing Strategies of SME Textile Manufactures in India – A Qualitative Perspective: Surviving and Thriving: Fashion Marketing Strategies for SME Textile Manufactures in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
SME textile manufactures play an important role in the economy of the country. Textile manufactures is an very important part of that sector and fashion runs hand in hand with that and so does fashion marketing. This paper focuses on the fashion marketing strategies that are used by fashion marketers to market the SME textile industry products such as apparels and garments to generate revenue and opportunities for the SME industry. This paper gives you a qualitative approach of the marketing mix tools and techniques of fashion product, fashion promotion, fashion place, fashion price. And the way those help in the marketing of the SMEs products. This helps in understanding the strategy used by the SMEs for marketing and what are the different ways through which they do it in a reasonable way as the investment and turnover to the SMEs are comparatively low. And with already the big players capturing the market how can they still survive and are surviving in the market only because of those marketing strategies.